Do I pass to my friend or the best player? The influence of psychological variables on passing and performance in field hockey - Spencer, K.; Griffin, M. (International Journal of Performance Analysis in Sport, 2013)
The purpose of the current study was to investigate the relationship of player-passing in field hockey with friendship affiliation, cohesiveness and performance. Indicators measured were; Performance (end of season results), Team A (N = 15) (61%wins) and Team B (N = 12) (27% wins); Cohesiveness was measured using the GEQ (Carron et al, 1985); Playerpassing through notational analysis of match play and friendship affiliation using a socialisation questionnaire. Results suggested that the higher ranked team had greater cohesion and friendship affiliation. The 'degree to which the team likes the individual' was shown to have a strong correlation with objective measures of performance. There was a strong relationship between passing and friendship affiliation. Lower ranked team passed most to their 'perceived best' player, whereas high ranking team passed to a wider range of players, implying they chose to pass to their 'best placed' rather than 'perceived best' players. The implications for team sport coaches is to encourage opportunities in training for players to develop positive friendship affiliation to take advantage of its positive influence on player-passing decision-making during match play.